1987
DOI: 10.1007/bf01092204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blanching and drying methods on the nutritional and sensory quality of leafy vegetables

Abstract: The nutrient retention and sensory quality factors of vegetables blanched by two methods and solar-dried or dried in the cabinet dryer were evaluated. The type and conditions of the blanching treatment prior to drying affect the retention of ascorbic acid, carotene, and ash in the dried vegetables. The sun-dried vegetables had inferior colour, texture and acceptibility compared to the vegetables dried in the cabinet dryer. There were significant differences in the rehydration and drying ratio of the dried vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 6 publications
6
26
0
Order By: Relevance
“…Regarding ash content, with the exception of V. nigando (6.05%), all other species in the present study have appreciably high level of ash content. This is consistent with the reported fact that most leafy vegetables are rich in minerals- Onayemi and Badifu (1987) reported such high values as 25.1% ash in Amaranthus hybridus and 27.32% ash in Celosia arqentia. Since total carbohydrate and lipid were low, these leafy vegetables cannot be regarded as energy food.…”
Section: Resultssupporting
confidence: 81%
“…Regarding ash content, with the exception of V. nigando (6.05%), all other species in the present study have appreciably high level of ash content. This is consistent with the reported fact that most leafy vegetables are rich in minerals- Onayemi and Badifu (1987) reported such high values as 25.1% ash in Amaranthus hybridus and 27.32% ash in Celosia arqentia. Since total carbohydrate and lipid were low, these leafy vegetables cannot be regarded as energy food.…”
Section: Resultssupporting
confidence: 81%
“…Sweet potato, pumpkin, cowpea, peanut and amaranth greens have been reported to be good sources of provitamins A [2,9,10]. Various levels of /%carotene, o~-carotene and total carotenoids have been reported [2,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These vegetables form an essential component of the meal by providing variety and a good source of provitamin A carotenoids, ascorbic acid, thiamin, riboflavin, minerals and dietary fiber [1][2][3]. They are the most reliable and cheapest sources of dietary vitamin A that are affordable by low income families ] 4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In vegetables all high fiber vegetables, among which cluster bean (guar) stands first. Green leafy vegetables are also known to be low GI [2]. Some earlier studies reported tubers also show low GI after consumption [3].…”
Section: Introductionmentioning
confidence: 97%